Global Warming: A Comprehensive Examination - Jaylen Keniah (GoAcademica Research & Publishing, 2023)
Global warming, a phenomenon characterized by the gradual increase in the Earth's average temperature, has emerged as one of the most pressing environmental challenges of our time. This scientific journal article delves into the multifaceted aspects of global warming, encompassing its causes, consequences, and potential solutions. By exploring the latest research findings, we aim to provide a comprehensive understanding of this critical issue and underscore the urgency for collective action to mitigate its adverse effects.